Evaluations on PM2.5 Concentrations and the Population Exposure Levels for Local Authorities in South Korea during 2015͠2017 - Son, Kyuwon; Kim, Eunhye; Bae, Minah; You, Seunghee; Kang, Yoon Hee; Kim, Hyun Cheol; Kim, Byeong Uk; Kim, Soontae (Journal of Korean Society for Atmospheric Environment, 2020)
The ambient concentration of an air pollutant can represent how bad air quality is aggravated, but local authorities may need the alternative indicator to show the urgency of air quality improvement in terms of the personal exposure. In this study, we compare PM2.5 concentration and the population exposures at the municipal and provincial authority levels in South Korea. For this purpose, we calculated three PM2.5 exposure indicators (i.e. PM2.5 concentration, Total Population Exposure; TPE, Population Weighted Exposure; PWE) for each municipal and provincial authority in South Korea during 2015-2017. The Kriging spatial interpolation was applied to fill out the spatiotemporal scarcity of the surface measurements. Jeonbuk presented the highest period-mean PM2.5 concentration (27.2 μg/m3) among 17 provinces while 15 municipal authorities in Jeonbuk show the intra-provincial variation as large as 6.4 μg/m3 (24.8 μg/m3͠31.2 μg/m3). Meanwhile, the TPE value, which means the authority’s total health burden, was highest in Gyeonggi owing to the high gross population. The PWE, which represents individual population exposure, was highest in Jeonbuk (13.9 μg/m3). The PWEs of municipal authorities in Jeonbuk ranged from 9.8 (Muju) to 17.0 μg/m3 (Iksan). When sorted, three exposure indicators for an authority placed in different rankings. However, there exist some provincial or municipal authorities that consistently take high rankings for all those indicators. It implies that urgent air quality improvement plans should be implemented to minimize the population exposure in those authorities.
Keywords: Annual mean concentration; PM2.5; Population exposure; PWE; TPE